2020
DOI: 10.1177/1350507620924162
|View full text |Cite
|
Sign up to set email alerts
|

‘Upon the gears and upon the wheels’: Terror convergence and total administration in the neoliberal university

Abstract: University governance is becoming increasingly autocratic as marketization intensifies. Far from the classical ideal of a professional collegium run according to academic norms, today’s universities feature corporate cultures and senior leadership teams disconnected from both staff and students, and intolerant of dissenting views. This is not a completely new phenomenon. In 1960s America, senior leaders developed a technocratic and managerialist model of the university, in keeping with theories around the ‘con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 59 publications
1
65
0
2
Order By: Relevance
“…The rising discontent of academic communities has been accepted as collateral damage -or, on a more pessimistic note, as an expected result of the de-democratising exercise that was deliberately aimed at restraining self-government. In this sense our findings suggest disempowering administrative models might contribute not only to rising levels of fragility among academics (Anderson 2008;Knights and Clarke 2014;McCann et al 2020), but also more severely to the authoritarian and anti-democratic tendencies that have gained strength in our societies. If universities in a stable and developed country like Finland, with their highly-educated staffs, are not perceived as being capable of exercising democracy, we can only wonder how the rest of the society and its democratic capabilities are perceived in the same regard.…”
Section: Resultsmentioning
confidence: 72%
“…The rising discontent of academic communities has been accepted as collateral damage -or, on a more pessimistic note, as an expected result of the de-democratising exercise that was deliberately aimed at restraining self-government. In this sense our findings suggest disempowering administrative models might contribute not only to rising levels of fragility among academics (Anderson 2008;Knights and Clarke 2014;McCann et al 2020), but also more severely to the authoritarian and anti-democratic tendencies that have gained strength in our societies. If universities in a stable and developed country like Finland, with their highly-educated staffs, are not perceived as being capable of exercising democracy, we can only wonder how the rest of the society and its democratic capabilities are perceived in the same regard.…”
Section: Resultsmentioning
confidence: 72%
“…There were regular and breathless announcements about the ambition to become a 'top 20' business school by a Head of School who was styling himself as 'Dean'; at the same time, that there was a tangible sense of loss and anger amongst academic staff. In a way that was very similar to other university change processes (see McCann et al, 2020;Parker, 2014), the messaging from the school, college and university had taken on an increasingly bright and corporate tone, with announcements about various initiatives that seemed largely disconnected from the experience of most employees. A school re-branding exercise was undertaken in 2012 which suggested that the 'sub-brand' image should be based around the four pillars of 'reputation ', 'collaborative', 'open' and 'real'.…”
Section: Utopia Undonementioning
confidence: 87%
“…This increasingly vies with a 'utilitarian' logic associated with strategic research and such concepts as the entrepreneurial (and occasionally civic) university, a logic which is particularly engrained in research intensive universities (Shields and Watermeyer, 2018). Finally, a 'managerial' logic, aligned with new public management practices (Docherty, 2016), reflects universities as increasingly bureaucratic, centralised and competitive organisations (Martin, 2016;McCann et al, 2020). Such logics heavily influence and configure behaviours and practices, which over time become embedded, routinised and repetitive, in turn maintaining institutions 1 associated with them (Lawrence and Suddaby, 2006).…”
Section: The Context For Ri Institutionalisationmentioning
confidence: 99%